Analisis Sistem Sadar Lingkungan (Sidarling) Melalui Perspektif E-Government di Kota Denpasar - I Putu Adi Permana Putra; Ni Putu Dinda Kalpika Putri (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
Globalization provides changes and challenges in utilizing knowledge and technology. Digitalization is expected to be able to be integrated into solving various public problems, one of which is providing public services and realizing smart cities. The waste problem often becomes a public polemic in its solution; this has become the concern of the Denpasar City government by presenting an innovative waste management system. SIDARLING (Information System Awareness and Concern for the Environment) is a form of waste management effort that invites urban residents to save their household waste through a web-based system and mobile application. The focus of this study is to analyze SIDARLING as a form of public service from an e-government perspective. This study used a qualitative descriptive method with data collection techniques through observation and literature study, as well as conducting qualitative data analysis. The results of the study show that SIDARLING is a form of e-government-based public service that focuses on waste management. Theoretically, it shows that SIDARLING has fulfilled the support, capacity, and value elements of its sustainability. This system is a form of government governance in the form of a new public service in digital-based waste management in Denpasar City.